2004
DOI: 10.1111/j.1365-4632.2004.02429.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis: successful treatment with itraconazole

Abstract: Background Leishmaniasis is a disease produced by several species of protozoa of the Leishmania genus. These protozoa are injected into the human bloodstream by sandflies. The symptomathology, either cutaneous, mucocutaneous or visceral, depends on the infective species and the immune status of the patient. Antimonial drugs are the mainstay treatment for all the clinical forms of the disease. Amphotericin B is the second-choice drug. MethodsWe report two clinical cases of cutaneous leishmaniasis treated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
18
0
5
Order By: Relevance
“…Posaconazole is structurally similar to itraconazole, has an extended range of antifungal activity, and superior pharmacokinetic properties, but its oral bioavailability is extremely variable (46). Both posaconazole and itraconazole have been demonstrated effective against cutaneous leishmaniasis in several human clinical trials (12)(13)(14). Recently, our group showed the potent in vitro effects of itraconazole and posaconazole against Leishmania amazonensis (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posaconazole is structurally similar to itraconazole, has an extended range of antifungal activity, and superior pharmacokinetic properties, but its oral bioavailability is extremely variable (46). Both posaconazole and itraconazole have been demonstrated effective against cutaneous leishmaniasis in several human clinical trials (12)(13)(14). Recently, our group showed the potent in vitro effects of itraconazole and posaconazole against Leishmania amazonensis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the potent effects of different ergosterol biosynthesis inhibitors (EBIs) on these microorganisms, as these agents interfere with some essential steps in the ergosterol biosynthesis pathway (10). Itraconazole (ITZ) and posaconazole (POSA), two well-known azoles that inhibit the enzyme sterol C-14␣-demethylase (CYP51) and are frequently used as antifungal agents, also have effects in vitro and in vivo against trypanosomatids, including organisms from the Leishmania and Trypanosoma genera (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Recently, we demonstrated that ITZ and POSA have a potent effect against L. amazonensis, inhibiting its growth, disrupting mitochondrial function, and affecting the ultrastructure of several organelles (17).…”
mentioning
confidence: 99%
“…18 Eventually, we offered itraconazole (200 mg twice daily for 6 weeks) as a second-line treatment, a therapy shown to have modest success in CL. 4,[22][23][24][25] Fig 1 shows the ThermoMed device, a radiofrequency heat delivery system in which two prongs are placed over anesthetized lesions in a grid-like fashion (approximately every 1 cm 2 ) for 30-second treatment periods at the target temperature until the entire lesion, and up to 0.5 to 1 cm of normalappearing surrounding skin, has been treated. 14,26 The target temperature between the prongs is 508C.…”
Section: Patients Methods and Treatmentsmentioning
confidence: 99%
“…Oral administration of miltefosine and the IM administration of paromomycin and pentamidine are also used for leishmaniasis [37, 4042]. In addition, certain azole compound normally used as antifungal agents including fluconazole and itraconazole are also used in treatments for both CL and MCL [43, 44]. …”
Section: Treatments For the Diseasementioning
confidence: 99%